Produto a base de própolis para bezerras lactentes - Casimiro, Tiago Rodrigues (2008)
The objective was to evaluate the addition of hidroalcohol propolis extract LLOSA2 and LLOSC3 that could be a substitute for lasalocid ionofore to Holstein calves fed from birth to weaning (60 days) with milk and concentrate (20% of CP) . It was used a totally random experimental design with three treatments and ten replication to evaluate animal performance and four repetitions to estimate total digestibility of diets. The calves had a dry matter intake varying from 987.15 g/d to 1,104.25 g/d for control and LLOS A2 treatments and a daily weight gain that varied from 674 to 738 g for control and LLOS C3 treatments, respectively, without significant difference. The control and LLOS C3 treatments had a feed gain ration of 1.48 while LLOS A2 had a feed gain ratio of 1.53. The offered diet had a higher digestibility coefficient with values similar.